2011
DOI: 10.1016/j.jhep.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Patients with liver cirrhosis suffer from primary haemostatic defects? Fact or fiction?

Abstract: Patients with cirrhosis can have abnormalities in laboratory tests reflecting changes in primary haemostasis, including bleeding time, platelet function tests, markers of platelet activation, and platelet count. Such changes have been considered particularly relevant in the bleeding complications that occur in cirrhosis. However, several studies have shown that routine diagnostic tests, such as platelet count, bleeding time, PFA-100, thromboelastography are not clinically useful to stratify bleeding risk in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(171 citation statements)
references
References 144 publications
(144 reference statements)
2
163
1
5
Order By: Relevance
“…In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5]. In addition, PVT in liver transplant candidates correlated with increased mortality after liver transplantation [206].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 95%
See 1 more Smart Citation
“…In these patients, the rate of spontaneous recanalization of portal veins was exceptionally high (70%), compared with only 1/41 in the prospective study by Luca et al [202]. Retrospective studies [43,181,203,205] yielded discordant data but overall indicated poorer survival in patients with stable or progressive PVT, if left untreated [2,4,5]. In addition, PVT in liver transplant candidates correlated with increased mortality after liver transplantation [206].…”
Section: Impact Of Portal Vein Thrombosis On the Natural History Of Cmentioning
confidence: 95%
“…The net effect of these changes is a rebalanced hemostasis. However, this hemostatic profile is unstable, and patients can be tipped toward both bleeding and thrombosis under certain conditions [1][2][3][4][5]. Thus, there is growing evidence that proper understanding of the hemostatic pathways in liver disease requires a global perspective which account for the complexity of hemostasis, with dynamic interactions between pro-coagulant and anti-coagulant factors.…”
Section: Introductionmentioning
confidence: 99%
“…It assesses the risk of thrombosis, but has never been used to assess the risk of bleeding [16] . The measurement of soluble activation markers assesses the presence of products released by platelets (soluble p-selectin, PF-4, beta-TGG, soluble CD40L).…”
Section: Platelet Function Assaymentioning
confidence: 99%
“…It is a systematic measurement of the degree of platelet activation, but for several reasons it may lead to artifacts. It helps to predict the risk of thrombosis, but does not predict the risk of bleeding [16] . The platelet adhesion test under flow conditions simulates the in vivo platelet function using standardized reconstituted blood and measures the adhesion of platelets to the subendothelium [17] .…”
Section: Platelet Function Assaymentioning
confidence: 99%
“…In chronic liver disease, there is a decrease in number of circulating platelets along with thrombocytopathy (platelet dysfunction). This is considered to be multifactorial, which includes pooling of platelets and sequestration in the spleen, presence of antiplatelet glycoprotein IIb-IIIa antibodies in cirrhosis patients, myelosuppression, shorter half-life and rapid turnover secondary to splenic destruction, increased platelet consumption secondary to sustained low grade DIC and lower levels of hepatic thrombopoetin production [9]. Qualitative defects in platelet function also prevail in cirrhosis patients.…”
Section: Platelets and Liver Diseasementioning
confidence: 99%